Fractal Analysis of Subchondral Cyst at Mandibular Condyle Detected on Panoramic Radiograph in A Group of Thai Population - Wijanarko, Aloysius Putut; Srimawong, Preeyaporn; Pornprasertsuk-Damrongsri, Suchaya; Janhom, Apirum (UI Scholars Hub, 2022)
Objectives: This study aimed to analyze subchondral cyst on the mandibular condyle using fractal dimension (FD) measurement on a panoramic radiograph. Methods: This retrospective study examined 15 patients aged 24 to 75 years who had undergone panoramic radiography and cone-beam computed tomography on both sides of the mandibular condyles, between January 2013 and November 2017, in the Oral and Maxillofacial Radiology Clinic, Dental Hospital, Mahidol University. These 15 patients, all of whom had a subchondral cyst on one side of the mandibular condyle, constituted both the study and control groups: the 15 affected sides constituted the study group, and the 15 unaffected sides constituted the control group. The FD of both groups was calculated by two investigators using ImageJ version 2.0x. Results: The average age of the subjects was 47.47 ± 15.99 years. The mean FD value was 1.306 ± 0.133 in the study group and 1.409 ± 0.858 in the control group. The FD values were significantly different between these groups (p-value 0.016). Conclusion: The FD values of mandibular condyle were lower in patients with subchondral cysts than in healthy patients. The fractal analysis provided clinicians with extra information regarding the condition of the subchondral cyst as an early sign of osteoarthritis on panoramic radiographs.